Acceleration and sprint profiles of a professional elite football team in match play - Ingebrigtsen, J.; Dalen, T.; Håvard Hjelde, G.; Drust, B.; Wisløff, U. (European Journal of Sport Science, 2015)
The aim of this study was to characterise the acceleration and sprint profiles of elite football match play in one Norwegian elite football team (Rosenborg FC). Fifteen professional players in five playing positions took part in the study (n = 101 observations). Player movement was recorded during every domestic home game of one full season (n = 15) by an automatic tracking system based on microwave technology. Each player performed 91 ± 21 accelerations per match, with a lower number in the second compared with the first half (47 ± 12 vs. 44 ± 12). Players in lateral positions accelerated more often compared to players in central positions (98.3 ± 20.5 vs. 85.3 ± 19.5, p < 0.05). Average sprint distance was 213 ± 111 m distributed between 16.6 ± 7.9 sprints, with no differences between first (106 ± 60 m, 8.2 ± 4.2 sprints) and second halves (107 ± 72 m, 8.3 ± 4.8 sprints). Players in lateral positions sprinted longer distances (287 ± 211 m vs. 160 ± 76 m, p < 0.05) and tended to sprint more often (21.6 ± 7.8 vs. 13.0 ± 5.7, p = 0.064) compared to players in central positions. We found more walking and less of the more intense activities during the last third of the season compared to the first. The main finding in this study was that Norwegian elite players had substantially less number of accelerations and fewer but longer sprints than previous studies reported for higher-ranked leagues. Also, less high-intensity activity was found towards the end of the season. Ultimately, these data provide useful information for the fitness coach (1) in planning of position-specific football training and (2) to avoid the decline in high-intensity activities the last third of the competitive season.